Population pharmacokinetics of favipiravir in patients with COVID‐19. (17th August 2021) - Irie, Kei; Nakagawa, Atsushi; Fujita, Hirotoshi; Tamura, Ryo; Eto, Masaaki; Ikesue, Hiroaki; Muroi, Nobuyuki; Fukushima, Shoji; Tomii, Keisuke; Hashida, Tohru
Abstract: The antiretroviral drug favipiravir (FPV) inhibits RNA‐dependent RNA polymerase. It has been developed for the treatment of the novel coronavirus (severe acute respiratory syndrome coronavirus 2) infection disease, coronavirus disease 2019 (COVID‐19). However, its pharmacokinetics in patients with COVID‐19 is poorly understood. In this study, we measured FPV serum concentration by liquid chromatography–tandem mass spectrometry and conducted population pharmacokinetic analysis. A total of 39 patients were enrolled in the study: 33 were administered FPV 1600 mg twice daily (b.i.d.) on the first day followed by 600 mg b.i.d., and 6 were administered FPV 1800 mg b.i.d. on the first day followed by 800 mg or 600 mg b.i.d. The median age was 68 years (range, 27–89 years), 31 (79.5%) patients were men, median body surface area (BSA) was 1.72 m 2 (range, 1.11–2.2 m 2 ), and 10 (25.6%) patients required invasive mechanical ventilation (IMV) at the start of FPV. A total of 204 serum concentrations were available for pharmacokinetic analysis. A one‐compartment model with first‐order elimination was used to describe the pharmacokinetics. The estimated mean clearance/bioavailability (CL/F) and distribution volume/bioavailability (V/F) were 5.11 L/h and 41.6 L, respectively. Covariate analysis revealed that CL/F was significantly related to dosage, IMV use, and BSA. A simulation study showed that the 1600 mg/600 mg b.i.d. regimen was insufficient for the treatment of COVID‐19 targeting the 50% effective concentration (9.7 µg/mL), especially in patients with larger BSA and/or IMV. A higher FPV dosage is required for COVID‐19, but dose‐dependent nonlinear pharmacokinetics may cause an unexpected significant pharmacokinetic change and drug toxicity. Further studies are warranted to explore the optimal FPV regimen.